The Development of Podcast-Based-Audio Learning in Material Introducing Ourselves at 10th Grade SMA Muhammadiyah 1 Pekanbaru - Hafra Hanum; Siti Niah; Pahmi Pahmi (Journal of Education and Learning Research, 2023)
This Podcast development research aims to produce a quality Podcast with the eligibility criteria for teaching materials and to determine the feasibility of the product based on the assessment of the material validator, media validator and students. This type of research is development research with ADDIE research model. The practicality test was carried out on students of SMA Muhammadiyah 1 Pekanbaru in the first semester (I) of the 2022/2023 academic year. Practicality test subjects consisted of 32 students to test the practicality of Podcast products designed with anchor applications. The assessment results obtained from the media validator are categorized as "very good" for use with an average of 4.61. The material validator assessment are also categorized as "very good" with an average material validator of 4.65. Furthermore, the practicality of the products carried out is in the category of practical use with an average Overall 4.56 which are in the very decent category. Based on the results of the validity and practicality tests, it can be concluded that the Podcast product is ready to be developed and is practically used in the learning process in particular the process of learning English on Introducing Ourselves material.